(untitled) - Blancas, Luis C. (Washington, D.C., 2014)
This report argues that promoting the use of waterborne transport in Vietnam’s freight logistics can be an effective way of both facilitating economic growth and reducing the emission of greenhouse gases and local pollutants. In particular, it shows that investments in capacity expansion and better maintenance provision at the country’s main navigable waterways and coastal shipping routes can result in logistics cost savings, which promote trade and drive growth. But they would also result in meaningfully lower emissions in a sector that remains less green than it could be, on account of the use of relatively small and inefficient vessels.
Keywords: Inland water transportation,Giao thông vận tải thuỷ nội địa; Economic aspects; Vietnam,Việt Nam